LINGUOCULTURAL APPROACHES IN TRANSLATION: LINGUOCULTURAL APPROACHES IN TRANSLATION - Erimbetova, Shakhzada (Журнал иностранных языков и лингвистики, 2025)
In today’s globalized world, translation is not merely the process of converting words from one language into another. Rather, it involves the transmission of culture, values, and context from one linguistic community to another. The key to fostering strong intercultural communication competence skills lies within the classroom itself [1; 214]. Therefore, translation education must go beyond the structural and semantic levels of language to include the cultural dimensions that influence meaning. In this regard, linguocultural approaches have gained significant importance in training. This article explores the principles, significance, and practical application of linguocultural approaches in translation education, emphasizing the need for culturally competent translators in the 21st century.